Linear-Structure Single-Atom Gold(I) Catalyst for Dehydrogenative Coupling of Organosilanes with Alcohols - Kadam, Ravishankar G; Medved', Miroslav; Kumar, Subodh; Zaoralová, Dagmar; Zoppellaro, Giorgio; Bad'ura, Zdeněk; Montini, Tiziano; Bakandritsos, Aristides; Fonda, Emiliano; Tomanec, Ondřej; Otyepka, Michal; Varma, Rajender S; et al. (ACS catalysis, 2023)
A strategy for the synthesis of a gold-based single-atom catalyst (SAC) via a one-step room temperature reduction of Au(III) salt and stabilization of Au(I) ions on nitrile-functionalized graphene (cyanographene; G-CN) is described. The graphene-supported G(CN)-Au catalyst exhibits a unique linear structure of the Au(I) active sites promoting a multistep mode of action in dehydrogenative coupling of organosilanes with alcohols under mild reaction conditions as proven by advanced XPS, XAFS, XANES, and EPR techniques along with DFT calculations. The linear structure being perfectly accessible toward the reactant molecules and the cyanographene-induced charge transfer resulting in the exclusive Au(I) valence state contribute to the superior efficiency of the emerging two-dimensional SAC. The developed G(CN)-Au SAC, despite its low metal loading (ca. 0.6 wt %), appear to be the most efficient catalyst for Si-H bond activation with a turnover frequency of up to 139,494 h-1 and high selectivities, significantly overcoming all reported homogeneous gold catalysts. Moreover, it can be easily prepared in a multigram batch scale, is recyclable, and works well toward more than 40 organosilanes. This work opens the door for applications of SACs with a linear structure of the active site for advanced catalytic applications.